Depressive symptoms and associated factors in an older Spanish population positively screened for disability. (11th September 2012) - Damian, Javier; de, Jesús; Almazán, Javier; Comín‐Comín, Magdalena; Quintanilla, Miguel A.; Lobo, Antonio
<x xml:space="preserve">Abstract</x> Objectives To measure the prevalence of depressive symptoms and its association with a comprehensive set of variables and to study the potential modifying effects of sex and age. Methods In a cross‐sectional study, subjects who tested positive to the 12‐item World Health Organization disability screening tool were selected from a probabilistic sample of persons aged 65 years or older in a rural area of Spain. Measurements included EURO‐D depression scale, socio‐demographics, habits, anthropometrics, medical history, cognition, disability, functional dependence, self‐rated health and pain. Logistic regression models were used to obtain adjusted odds ratios (aORs) and 95% confidence intervals (95% CIs) for the association between depression and variables. The modifying effects of age and sex were assessed. Results Prevalence (95% CI) of current depressive symptoms among the 438 participants was 35.8% (31.3–40.3%). Depressive symptomatology was higher among women (aOR = 2.98). An inverse association was observed with alcohol (aORs of 0.52 and 0.27 for consumption of 1–2 and >2 standard units/day, respectively, versus abstainers). Depressive symptomatology was associated with heart failure (aOR = 4.24), urinary incontinence (aOR = 2.68), ischemic heart disease (aOR = 1.87), poor self‐rated health and pain. Sex and age modified the effect of several variables. Conclusion Prevalence of depressive symptoms, albeit high, was less than expected. The consistently strong negative association between depressive symptoms and alcohol consumption warrants further in‐depth research. Awareness of effect modification by key variables, such as sex and age, may enable the probability of suffering depression to be more accurately assessed, with a view to performing a potential diagnostic work‐up. Copyright © 2012 John Wiley & Sons, Ltd.